Development of android-based scrapbook digital media material on the relationship between the image of the state emblem and the precepts of Pancasila - Syafira, Ade Chia; Saleh, Sarbaini; Mehta, Kunal (Program Pascasarjana Universitas Negeri Yogyakarta, 2024)
Currently, teachers only focus on using package books in teaching in the classroom. Without the sophistication of technology that is not combined with teaching media, it will form students who do not show enthusiasm and do not have character in the learning process. Therefore, researchers are interested in making android-based scrapbooks. This study aims to determine the scrapbook's feasibility, practicality, and effectiveness. This research is a research and development (R&D) with a model from 4-D to 3-D. The result of this research is that the value of Aiken's V calculation on the validation data of material experts is 0.903, and media experts of 0.8 are classified as suitable for use. Then, the results of V Aiken's calculation, student response data of 0.932 and teacher response data of 0.89 are classified as practical to use during learning. Meanwhile, the calculating-paired the t-testest and post-test with a t-count value = 6.18 and a t-table value = 2.039. Since t-count > t-table, it has a